Piilevät arktis-alpiinisissa puroissa : korkeuden vaikutus beta-diversiteettiin - Kallajoki, Liisa (Helsingfors universitet, 2015)
Beta-diversity describes the change of community composition between sites. It is an important, albeit poorly understood component of biodiversity, which often represents regional diversity more profoundly than local species richness. Studying the relationship between diatom community composition and elevation increases our understanding of the mechanisms governing regional diversity patterns. Traditionally small organisms with high population densities have been thought to be omnipresent, restricted only by prevailing environmental conditions, with no biogeographical patterns, unlike those found in macro-organisms. In this thesis beta-diversity will be studied on four elevational gradients (n=64) using Sørensen, Simpson and Morisita-Horn indices. Because the relative importance of spatial control and environmental variables vary across spatial scale, I examine the change in community composition between all the sites along the elevational gradient and at a smaller scale between adjacent sampling sites. The rate of distance decay will also be examined as the halving distance of community similarity. Since total species diversity is closely associated with species range size, I will also observe Rapoport's rule, which states that elevational ranges of species are generally wider at higher elevations than at lower elevations due to climatic variability. Linear regression and Mantel tests were the statistical methods used to study beta-diversity. Redundancy analysis (RDA) and cluster analysis were also used as multivariate methods. The effect of elevation on large scale species turnover was statistically very significant on all study gradients with both simple and partial Mantel tests (r=0.368–0.742 P=0.001). The effect of environmental variables was statistically very significant only in the Pyrenees, as opposed to the streams around the Kilpisjärvi area. The effect of elevation on small scale beta-diversity was statistically significant only in the Pyrenees (P=0.001) and Helligskogen (P<0.05). The halving ...